Ex vivo studies for the passive transdermal delivery of low-dose naltrexone from a cream; detection of naltrexone and its active metabolite, 6β-naltrexol, using a novel LC Q-ToF MS assay. (September 2015) - Dodou, Kalliopi; Armstrong, Andrew; Kelly, Ivan; Wilkinson, Simon; Carr, Kevin; Shattock, Paul; Whiteley, Paul
Abstract Naltrexone (NTX) is a long-acting opiate antagonist. Low-dose naltrexone (LDN) therapy has shown promising results in the treatment of several autoimmune disorders. Our aim was to formulate NTX into a cream for the delivery of LDN and develop an analytical technique for the quantification of NTX and its active metabolite 6-β-naltrexol (NTXol) during transdermal diffusion cell permeation studies. A 1% w/w NTX cream was formulated and drug permeation was examined over 24 h using static Franz diffusion cells mounted with pig skin. A Liquid Chromatography Quadrupole-Time of Flight Mass Spectrometry (LC-MS Q-ToF) method was developed for the detection of NTX and NTXol in the receptor solution, skin membrane and residual cream on the donor chamber after completion of the diffusion studies. The cream formulation exhibited steady state release of NTX over 24 h after an initial lag time of 2.74 h. The bioconversion of NTX to NTXol in the skin membrane was 1.1%. It was concluded that the cream may be an effective formulation for the sustained transdermal delivery of LDN. The novel LC Q-ToF MS method allowed the accurate measurement of NTX and NTXol levels across the diffusion cell assemblies and the quantification of NTX metabolism in the skin.